Production of palm kernel shell-based activated carbon by direct physical activation for carbon dioxide adsorption - Rashidi, N.A. (Springer Verlag, 2018)
The feasibility of biomass-based activated carbons has received a huge attention due to their excellent characteristics such as inexpensiveness, good adsorption behaviour and potential to reduce a strong dependency towards non-renewable precursors. Therefore, in this research work, eco-friendly activated carbon from palm kernel shell that has been produced from one-stage physical activation by using the Box-Behnken design of Response Surface Methodology is highlighted. The effect of three input parametersâtemperature, dwell time and gas flow rateâtowards product yield and carbon dioxide (CO2) uptake at room temperature and atmospheric pressure are studied. Model accuracy has been evaluated through the ANOVA analysis and lack-of-fit test. Accordingly, the optimum condition in synthesising the activated carbon with adequate CO2 adsorption capacity of 2.13 mmol/g and product yield of 25.15 wt is found at a temperature of 850 Â°C, holding time of 60 min and CO2 flow rate of 450 cm3/min. The synthesised activated carbon has been characterised by diverse analytical instruments including thermogravimetric analyser, scanning electron microscope, as well as N2 adsorption-desorption isotherm. The characterisation analysis indicates that the synthesised activated carbon has higher textural characteristics and porosity, together with better thermal stability and carbon content as compared to pristine palm kernel shell. Activated carbon production via one-step activation approach is economical since its carbon yield is within the industrial target, whereas CO2 uptake is comparable to the synthesised activated carbon from conventional dual-stage activation, commercial activated carbon and other published data from literature. Â© 2018 Springer-Verlag GmbH Germany, part of Springer Nature